Engineering Active Iron Sites on Nanoporous Bimetal Phosphide/Nitride Heterostructure Array Enabling Robust Overall Water Splitting. (20th December 2022) - Zhou, Xuan; Mo, Yuxue; Yu, Fang; Liao, Liling; Yong, Xinru; Zhang, Fangming; Li, Dongyang; Zhou, Qian; Sheng, Tian; Zhou, Haiqing
Abstract: Alkaline water electrolysis is a commercially viable technology for green H2 production using renewable electricity from intermittent solar or wind energy, but very few non‐noble bifunctional catalysts simultaneously exhibit superb catalytic efficiency and stability at large current densities for hydrogen and oxygen evolution reactions (HER and OER, respectively), especially for iron‐based catalysts. Given that iron is the most abundant and least expensive transition metal, iron‐based compounds are very attractive low‐cost targets as active electrocatalysts for bifunctional water splitting with large‐current durability. Herein, the in situ construction of a self‐supported Fe2 P/Co2 N porous heterostructure arrays possessing superb bifunctional catalytic activity in base is reported, featured by low overpotentials of 131 and 283 mV to attain a current density of 500 mA cm −2 for HER and OER, respectively, outperforming most of non‐noble bifunctional electrocatalysts reported hitherto. Particularly, this hybrid catalyst also displays an excellent overall water splitting activity, requiring low voltages of 1.561 and 1.663 V to attain 100 and 500 mA cm −2 with excellent durability in 1 m KOH, respectively. Most importantly, the catalyst is stable for >120 h, even when the current density is 500 mA cm −2, which is prominently superior to IrO2 (+) //Pt (−) coupled noble electrodes, and is among the very best bifunctional catalysts reported thus far. Detailed theoretical calculations reveal that the interfacial interaction between Fe2 P and Co2 N can further improve the H* binding energy at the iron sites. Abstract : Self‐supported Fe2 P/Co2 N porous heterostructure arrays are in situ constructed with abundant iron sites exposing at the surface, which presents superb bifunctional catalytic activity for hydrogen and oxygen evolution reactions in base, substantially expediting the overall water splitting at 500 mA cm −2 with only 1.663 V, prominently superior to IrO2 (+) //Pt (−) coupled electrodes and most of non‐noble bifunctional electrocatalysts.